Pengembangan Video Pembelajaran Berbasis Karakter Dalam Materi Operasi Bilangan Bulat Pada Siswa Kelas VII SMP Bina Bangsa Meliau - Viktoria Farida; Reni Astuti; Yudi Darma (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to develop a character-based instructional video on the topic of Integer Operations for seventh-grade students at Bina Bangsa Meliau Junior High School and to determine the validity, practicality, and effectiveness of the developed learning media. The instructional video was designed to enhance students' understanding of mathematical concepts while simultaneously fostering character values such as religiosity, honesty, hard work, and curiosity. This study employed a Research and Development (R&D) approach using the Borg and Gall development model, which was modified into seven stages: identifying potential and problems, data collection, product design, design validation, design revision, product testing, and product revision. The validation process involved two media experts and two subject matter experts, while the product trial was conducted with 24 seventh-grade students at Bina Bangsa Meliau Junior High School. Data were collected through expert validation questionnaires, student response questionnaires, and learning achievement tests. The data were analyzed descriptively using percentages to determine the validity, practicality, and effectiveness of the developed product. The results showed that the character-based instructional video met the criteria of being highly valid, with validation scores of 90.00% from media experts and 84.62% from subject matter experts. The practicality test yielded an average score of 92.41%, indicating that the video was highly practical. Furthermore, the effectiveness test demonstrated an improvement in students' learning outcomes, as reflected by an average achievement score of 77.34 and an increase in classical learning mastery from 25.00% to 87.50%, exceeding the predetermined standard for classical mastery.